From Arctic Science to International Law: The Road towards the Minamata Convention and the Role of the Arctic Council - Platjouw, Froukje Maria; Hovland Steindal, Eirik; Borch, Trude (Arctic Review on Law and Politics, 2018)
The Minamata Convention, which entered into force on 16 August 2017, is a global, legally binding instrument on mercury. The initiative on the Minamata Convention was mainly driven by research showing negative effects on human health and the environment in the Arctic. The Arctic Council, an intergovernmental forum promoting cooperation on Arctic issues, and its Working Group, AMAP, played an important role in the process leading up to international negotiations on the Minamata Convention. This paper elucidates the evolutionary process in which scientific knowledge, herded by an intergovernmental, regional forum, is involved and forms the basis for a legally binding agreement. The paper provides new insight on multilevel governance of the mercury issue and unravels the role that AMAP has played in this dynamic process.